La estructura organizacional y la influencia en la optimización de los servicios de la Federación Deportiva Provincial de Bolívar, Guaranda, año 2019 - Gutiérrez Michuy, Jessica Daniela (2020)
The research work is carried out in order to propose an organizational structure that fits the reality of the Provincial Sports Federation of Bolívar and that allows for the optimization of services. In the theoretical framework, the description of the problem was extended through documentary research, fundamental concepts were addressed in relation to the study variables, their regulations and location of the research object. The methodology used in the project corresponds to the field research, with which the respective information gathering was carried out, both from surveys, interviews and direct observation. With the data collected from the research, it was determined that the institution maintains an outdated organizational structure that is conditioning the fulfillment of goals and objectives set by the administration, due to the fact that it does not clearly define basic guidelines for proper management. Then we proceeded to design the Organizational Structure for Processes for the institution, which contains: strategic addressing, value chain, process map, structural organic, attributions and responsibilities of each work area, which constitute a contribution to better management and as a result adequate results in the optimization of the services of the Provincial Sports Federation of Bolívar. Once the investigation is finished, the Organizational Structure for Processes will be delivered to the General Administrator so that the pertinent instances decide whether it is convenient for the institution to approve and execute the proposal.